PERBANDINGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK DENGAN COMORBID HIPERTENSI DAN DENGAN DIABETES MELITUS YANG MENJALANI HEMODIALISA DI KLINIK HEMODIALISA PANDAONI MEDIKA - Indah Burdah Sari, (2021)
Background: End Stage Renal Disease or end-stage chronic kidney disease is a progressive and irreversible kidney organ disorder seen by a decrease in Glomerular Filtration Rate (GFR) function of less than 15 mL/min/1.73 m2 that occurs more than 3 months. Comorbid can influence level of quality of life of patients with End Stage Renal Disease. The most comorbid in end stage renal disease patients are hypertension and diabetes mellitus. Objective: To compare the level of quality of life of End Stage Renal Disease patients with comorbid hypertension and diabetes mellitus at the Pandaoni Medika Hemodialysis Clinic. Methods: The instrument used in this study was a Kidney Disease and Quality of Life (KDQOL-36) questionnaire. The sampling technique used the Non-Probability Sampling technique with 92 respondents. The approach used is cross sectional with the use of T-Independent analysis. Results: There is a difference between the quality of life of end stage renal disease patients with comorbid hypertension and comorbid diabetes mellitus in domain burden of kidney disease with P-Value = 0.001. The total value of the overall quality of life of end stage renal disease patients with comorbid hypertension is higher than end stage renal disease patients with comorbid diabetes mellitus.